Management of endocrine immune-related adverse events of immune checkpoint inhibitors: an updated review - Stelmachowska-Banaś, Maria; Czajka-Oraniec, Izabella (Endocrine Connections, 2020)
Immune checkpoint inhibitors (ICIs) belong to a new group of anticancer drugs targeting T-cell proteins involved in the activation of immune response toward malignancies. Their introduction into clinical practice was a milestone in modern cancer treatment. However, the significant advantage of ICIs over conventional chemotherapy in terms of therapeutic efficacy is accompanied by new challenges related to specific side effects. ICI-induced immune system activation could lead to the loss of self-tolerance, presenting as autoimmune inflammation and dysfunction of various tissues and organs. Thus, the typical side effects of ICIs include immune-related adverse events (irAEs), among which endocrine irAEs, affecting numerous endocrine glands, have been commonly recognized. This review aimed to outline the current knowledge regarding ICI-induced endocrine disorders from a clinical perspective. We present updated information on the incidence and clinical development of ICI-induced endocrinopathies, including the most frequent thyroiditis and hypophysitis, the rarely observed insulin-dependent diabetes mellitus and primary adrenal insufficiency, and the recently described cases of hypoparathyroidism and lipodystrophy. Practical guidelines for monitoring, diagnosis, and treatment of ICI-related endocrine toxicities are also offered. Rising awareness of endocrine irAEs among oncologists, endocrinologists, and other health professionals caring for patients receiving ICIs could contribute to better safety and efficacy. As immunotherapy becomes widespread and approved for new types of malignancies, increased incidences of endocrine irAEs are expected in the future.